WHEATGRASS (TRITICUM AESTIVUM LINN.): A POTENTIAL SUBSTITUTE OF HUMAN BLOOD IN TRADITIONAL SYSTEM OF MEDICINE - CHOUDHARY, SHAILJA; KAURAV, HEMLATA; CHAUDHARY, GITIKA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Wheatgrass (Triticum aestivum Linn.) refers to the young grass of the common wheat plant which belongs to the family Poaceae. It is known as the powerhouse of nutrients and vitamins. The juice of wheatgrass is known as “green blood” which contains an excessive amount of chlorophyll content (70% of the total chemical constituents), antioxidants, active enzymes, vitamins, and other vital nutrients which are used to enhance lungs and heart function. Wheatgrass juice is also taken as a supplementary diet to boost the immune system and provide strength to the human body. From reported studies, it is proved that molecules of human blood hemoglobin and wheatgrass chlorophyll contain the same structure and can act as a substitute for hemoglobin in hemoglobin deficiency conditions. It is a highly nutritive plant and is used to cure diseases such as cancer, diabetes, ulcer, rheumatoid arthritis, hyperlipidemia, thalassemia, anemia, kidney stone, asthma, digestive problems, and skin diseases. Pharmacologically, wheatgrass carries properties such as anti-diabetic, anti-allergic, antioxidant, anti-ulcer, anticancer, hepatoprotective, cardioprotective, anti-inflammatory, and antiarthritic properties. In this review paper, attempts have been made to provide a brief overview of wheatgrass, its pharmacological activities, and ayurvedic view.